Percutaneous drainage of hepatic abscesses. - Morelli, Raúl; Perrone, Luis; Maquieira, Gonzalo; Pin, Oscar; Petersen, Federico; Retich, Gizela (Cirugía del Uruguay, 1985)
During 1984, 5 pyogenic abscesses were detected and topographied. Based on preciseness of images the soundness of the way chosen was secured, diagnosis by aspiration being made and followed by subcutaneous drainage. lmmediate evolution was excellent with complete recovery in every case. An antibiotic treatment adequate to the germ was maintained al ali times. No recidivation or compiications in this series. Without mortality.